Summer - Saunders-Smith, Gail. frey50 (Mankato, MN. : Pebble books, 1998)
Simple text and photographs depict the weather, plants, animals, and activities of summer.
Includes bibliographical references and index.
73239
Keywords: Summer -- Juvenile literature; Summer